Վրեժխնդրությունն իբրև ընդվզում եղեռնագործության դեմ - Մխիթարյան, Արզիկ (ԱրՊՀ հրատ․)
The given article highlights the psychological aspect of the sense of revenge which was born as a protest against the atrocities committed. It is based on the real events of the Armenian Genocide В статье освещается психологический аспект чувства мести, рожденного как протест против совершенного зверства. Оно подтверждается фактами событий геноцида армян.
Keywords: Հայոց ցեղասպանություն; Արցախ